The Influence of Third-Party Fund, Total Assets, and BI7DRR Mobile Banking Transaction Values in Indonesia Islamic Banks - Puput Zahra; Nazhira Tasya Ghaissani; Neng Sofa Mawadatannasriah; Rahayu Juliandini; Rajab Sobarna; Haris Nugraha; Neni Sri Wulandari (Bulletin of Islamic Economics, 2026)
The rapid digital transformation in Indonesia’s banking sector has shifted financial transaction patterns toward mobile-based services. This study aims to analyze the effects of Third-Party Funds (DPK), Total Assets, and the BI 7-Day Reverse Repo Rate (BI7DRR) on the value of mobile banking transactions in Islamic banking in Indonesia. The study employs monthly secondary data covering the period from July 2020 to June 2025, consisting of 60 observations, and applies the Vector Error Correction Model (VECM) to examine both short-run and long-run relationships among variables. The Granger causality test results indicate the presence of unidirectional causality from DPK, total assets, and BI7DRR to the value of mobile banking transactions. The Johansen cointegration test confirms the existence of a long-run equilibrium relationship among the variables. The VECM estimation shows that, in the long run, total assets have a positive and significant effect on the value of mobile banking transactions, while DPK and BI7DRR do not have a significant effect. In the short run, the error correction coefficient (CointEq1 = −0.620366) indicates an adjustment speed toward equilibrium of 62%. The findings suggest that the expansion of Islamic banking assets plays a crucial role in driving digital transaction activity, while changes in monetary policy (BI7DRR) tend to influence transaction behavior primarily in the short run. These results provide implications for strengthening digital financial inclusion strategies through liquidity management and the enhancement of Islamic banking asset capacity.